Alyssum rossetii (Brassicaceae), a new species from the Aosta Valley in Italy based on morphological and genome size data - Španiel, Stanislav; Kaplan, Klaus; Bovio, Maurizio; Mártonfiová, Lenka; Cetlová, Veronika (Phytotaxa, 2018)
Alyssum rossetii, a stenoendemic madwort discovered on a mountain slope in the Valpelline valley (northern part of the Aosta Valley in the Pennine Alps), is described here as a new species. It is a perennial that is morphologically close to the Alyssum montanum-A. repens complex, with several hitherto neglected peculiar morphological characters. Here we present a full description of the new taxon, including information on its chromosome number, genome size and ecology, as well as a detailed morphological comparison of the new species with four related taxa occuring in the broader region, namely A. flexicaule, A. montanum, A. orophilum and A. rhodanense. Besides morphological differences, the new species also conspicuously differs from the other taxa in relative monoploid genome size. According to the IUCN Red List categories and criteria, it should be classified as Endangered.